A construction for resistant resolvable 3-designs without repeated blocks - Rudra, Sarita; Banerjee, Shakti; Kageyama, Sanpei (Utilitas Mathematica, 2006)
Block designs having the three properties, resolvability, multiplicity and no repeated blocks, are of statistical and/or combinatorial interest. A method of constructing a 2-multiple resolvable 3-design with no repeated blocks is here proposed with one example. The resistance property of such designs is also discussed.